Aktivitas Antibakteri Salep Dengan Bahan Aktif Ekstrak Kunyit, Kencur Dan Temugiring Terhadap Bakteri Staphylococcus Aureus - Bambang Yunianto; Titik Lestari; Agus Winarso (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: Antibacterial Activity, Skin ointment, Turmeric, Kaemferia galanga L, Curcuma heyneana. Indonesia is a country with a very high biodiversity. In the high diversity are stored potent plant potentials that can be extracted and utilized further. People are starting to realize the use of chemicals to solve life problems, especially health problems, in addition to expensive, can also cause adverse side effects for humans. Human life is always surrounded by microbes, either pathogenic or nonpathogenic. Many plants that have properties as antibacterial, such as turmeric, Kaemferia galanga L. and Curcuma heyneana. This research use turmeric, Kaemferia galanga L. And Curcuma heyneana extract, as active ingredient of skin ointment. This study aimed to know the extent to which the antibacterial activity of these three ointments against Staphylococcus aureus bacteria. This type of research was quasi experimental, with the design of Static Group Comparasion. Activity test with wells method with diameter 6,5 mm showed that the mean of clear zone were Kaemferia galanga L. (14,52 mm), turmeric (13,26 mm), Curcuma heyneana (7,89 mm), and control (6.49 mm)